2005
DOI: 10.1111/j.1742-4658.2005.04790.x
|View full text |Cite
|
Sign up to set email alerts
|

The specific delivery of proteins to human liver cells by engineered bio‐nanocapsules

Abstract: A drug and gene delivery system has long been considered important for drug discovery and pharmaceutical development. In particular, the establishment of a cellor tissue-specific targeting method is the latest area of focus. Although, viral vectors, such as those utilizing adenovirus or adeno-associated virus, have been developed for gene therapy, the cell specificity must be ameliorated. Some other problems, such as inflammation, neutralizing antibodies, the dangers of mass production, and insertional mutagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…These nanoparticles possess high gene transfer efficiency and show high specificity to human liver cells. 19,21 We have succeeded in loading several different genes into the particles, and then transferring these genes into human liver cells in vitro and in vivo. In addition, L nanoparticles are easily produced by recombinant yeast cells and large-scale production of the particles has already been established, 20,22 whereas large-scale manufacturing of clinical-grade viral vectors remains a significant obstacle that hampers its clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles possess high gene transfer efficiency and show high specificity to human liver cells. 19,21 We have succeeded in loading several different genes into the particles, and then transferring these genes into human liver cells in vitro and in vivo. In addition, L nanoparticles are easily produced by recombinant yeast cells and large-scale production of the particles has already been established, 20,22 whereas large-scale manufacturing of clinical-grade viral vectors remains a significant obstacle that hampers its clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The pre-S1 region of the L-protein, displayed on the surface as the specific ligand for receptor of human hepatocytes, certainly confers on the L-BNC the high infectivity to hepatocytes limited to humans and primates. Very recently, we have shown that the L-BNC efficiently delivers the gene for green fluorescence protein (GFP) and GFP protein to human liver cells in a cell type specific manner in vitro and in vivo (14,32). Thus, our engineered L-BNC was demonstrated to be an efficient delivery mimicking HBV.…”
Section: Engineered Bio-nanocapsule Has the Same Specific Infectivitymentioning
confidence: 92%
“…The gene of EGFP, an analogue mutant of GFP, fused to the 3' end of L gene, was expressed in mammalian COS-7 cells and the BNCs of L-EGFP fusion were produced and prepared. When infected, these L fusion particles showed green fluorescence only on the human hepatocytes (32), indicating that the L fusion particles have equivalent specific transfection efficiency due to the hepatocyte recognition site present in the pre-S1 region. No encapsulation procedure, such as electroporation, is required if the fusion strategy is available for the BNC.…”
Section: Engineered Bio-nanocapsule Can Deliver Substances To Target mentioning
confidence: 98%
“…HBV, a human liver-specific virus, contains three overlapping envelope genes in a single open reading frame, encoding for small, medium and large proteins in its 3.2-kb genome [91]. The large protein subunit of HBV can be isolated as an aggregate form of a phospholipoprotein vesicle with an average size of 80 nm, with a targeting motif for human hepatocytes specified by the sequence located in the amino-terminus of the large subunit [151]. These hybrid vesicles have been demonstrated as safe vehicles for delivery of genes with high ex vivo and in vivo transfection efficiencies, and high targeting specificity to human hepatocyte-derived cells [91,151].…”
Section: Cell Targetingmentioning
confidence: 99%
“…Several studies have demonstrated the feasibility of using various nanoparticles (BNPs, liposomal carriers, inorganic materials, etc.) tailored with ligands and small molecules to target different cell types for drug/gene delivery and cell imaging [56,137,151,152,164]. The nanosized probes can further be modified with chemical compounds, such as bioimaging agents (NIR fluorescent dyes, magnetic resonance imaging contrast agents) and drugs at high local concentrations to increase detection sensi- tivity and efficacy for therapeutic applications [166,187,188].…”
Section: Future Directionsmentioning
confidence: 99%